In vivo toxicities of the hospital effluent in Mahdia Tunisia - Sabrine Afsa; Ons Fekih Sallem; Nouha Ben Abdeljelil; Anouar Feriani; Mohamed Fadhel Najjar; Hedi Ben Mansour (IWA Publishing, 2021)
Hospital effluent (HE) is one of the most important sources of pharmaceuticals released into the environment. This kind of pollution is a recognized problem for both human health and aquatic life. Consequently, in the present study, we assessed the effects of untreated hospital effluent on mice via biochemical and histopathological determinations. Female mice were given free access to water bottles containing untreated HE at different dilutions for 21 days. Then clinical biochemistry and histopathology evaluation were conducted. Serum biochemistry analysis showed the presence of significant increase in cholesterol, triglycerides, glycaemia and total bilirubin. However, phosphatase alkaline and urea activities have been significantly decreased compared to the control group. No significant variation was observed for the rest of the studied parameters (high-density lipoproteins; low-density lipoproteins and uric acid). Additionally, multiple alterations, including cellular necrosis, leucocyte infiltration and congestion, were observed in different tissues of mice exposed to the tested HE. HIGHLIGHTS Hospital effluent (HE) exposure did not influence the total body weight of mice.; Sub-chronic exposure to the HE disturbed biochemical parameters in mice.; Histological abnormalities were observed in mice liver, kidney and heart sections.; Effluent toxicology.; Water contamination.;